1995
DOI: 10.1159/000098761
|View full text |Cite
|
Sign up to set email alerts
|

Early Effects of Gamma Knife Surgery on Malignant and Benign Intracranial Tumors

Abstract: To assess the early response of intracranial tumors to Gamma Knife surgery, we performed a prospective investigation of 42 patients treated by Gamma Knife surgery for different types of intracranial tumors. The clinical condition, tumor volume, treatment results and their temporal correlation with the irradiation were analyzed, based on MRI performed on the same MR scanner. Volume reduction in the tumors measured at the latest follow-up ranged from 0.2 to 100%. All except 1 malignant tumor showed decreasing si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

1997
1997
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 0 publications
0
8
0
2
Order By: Relevance
“…Our method is to measure the tumor's area on every slice. The sum of the areas was multiplied by thickness of MR image (0.3 cm) thus giving the total tumor volume [3]. In 80 meningiomas, the baseline tumor volumes (BTVs) were stratified into 4 groups: BTV 1 (=5 ml, n>38), BTV 2 (5-10 ml, n>21), BTV 3 (10-15 ml, n>14), and BTV 4 (15-20 ml, n>7).…”
Section: Methodsmentioning
confidence: 99%
“…Our method is to measure the tumor's area on every slice. The sum of the areas was multiplied by thickness of MR image (0.3 cm) thus giving the total tumor volume [3]. In 80 meningiomas, the baseline tumor volumes (BTVs) were stratified into 4 groups: BTV 1 (=5 ml, n>38), BTV 2 (5-10 ml, n>21), BTV 3 (10-15 ml, n>14), and BTV 4 (15-20 ml, n>7).…”
Section: Methodsmentioning
confidence: 99%
“…The increased application of radiosurgery in the treatment of meningiomas has created a demand for higher precision in diagnostic imaging in pretreatment planning for postoperative tumor remnants or recurrences (14,43,44). The traditional criteria for the assessment of surgical results-eradication of the tumor-cannot be applied in radiosurgery, and arrest of tumor growth is considered a success (43).…”
Section: Discussionmentioning
confidence: 99%
“…The past study showed that MRI or CT could show the tumor diminution 1-2 months later radiotherapy and about 4%-40% of brain tumors were seen to enlarge on MRI during radiotherapy, which is suggestive of breakdown of the blood-brain barrier (BBB) [7][8][9] . So conventional CT and MRI have disadvantage evaluation in curative effect, especially early curative effect of radiotherapy in patients with brain tumors.…”
Section: Discussionmentioning
confidence: 99%